Materials and methods of clinical research - Kholikov Azizbek Alimurodovich; Fattayeva Dilorom Rustamovna; Shermatov Eldor Abrorjonovich; Shermatova Kamola Hamraevna (Zien Journals, 2023)
It was developed by the Dentium company in the experimental and clinical part of scientific research"OsteontmIISollagen"Regenerative properties of the drug and specificity of use were studied
Keywords: OsteontmIISollagen; рatients; chemical composition; Sinus lifting